Tradisi Lisan dalam Melestarikan Lingkungan Alam di Kampung Adat Dukuh, Desa Ciroyom, Kecamatan Cikelet, Kabupaten Garut - Nyai Kartika; Reiza D. Dienaputra; Susi Machdalena; Awaludin Nugraha; Nani Sriwardani (Mudra Jurnal Seni Budaya, 2022)
Life in kampung adat is always interesting to study. Not only it has different culture than what is fostered by the community in general, kampung adat also has local wisdom that is ardently upheld by its community. One example is an oral tradition in Kampung Adat Dukuh, Ciroyom Village, Cikelet Subdistrict, Garut District, which is known as Uga Mandeling. The oral tradition contains local wisdom in preserving the natural environment. This study aims to further explore Uga Mandeling oral tradition and the extent to which it affects the life of the community. This study applied a historical method with four stages, namely heuristics, criticism, interpretation, and historiography, to analyze Uga Mandeling in Kampung Adat Dukuh. The results show that, in addition to maintaining the natural environment, Uga Mandeling also contains an appeal to lead a harmonious life with other communities as well as the government. This study is expected to contribute to the relevant literature, particularly related to Kampung Adat Dukuh.